#TITLE_ALTERNATIVE# - RAHMAWATI (nim:15310019), AISA
Transfer Depot can affect the physical, chemical, biological, and social environment. Research is required to know the quality of environment near Transfer Depost, such as grround water and surface water (by laboratory test), flies counting, and inverview with respondent. There are six locations of transfer depots in this research, located in Tamansari, Suci, Arcamanik, Tegalega, Ciroyom, and Antapani. The result of ground water and surface water laboratory test show that organic matter and COD in samples are high. The highest organic matter is 6527.59 mg/L (surface water 2 Antapani) and the highest COD is 1920 mg/L (surface water 2 Tegalega). COD and organic matter are high caused by contamination of leachate from the transfer depot. Flies counting done in four places in every transfer depot. The highest average flies population is in Ciroyom (32.8 flies) and the lowest population is in Arcamanik (11.5 flies). From the interview, respondents explained that transfer depot caused affect to the environment such as disturb the traffic, smell, not aesthetics, make ground wet, also increase the population of flies. But there are some positive aspect of transfer depot for respondent because transfer depot is a facility of waste dump, also for working land garbage man. From this study it can be concluded that the transfer depot gives various influences on the environment, such as decreasing quality of surface water and groundwater, increasing the fly population index, also gives social impacts for the surrounding residents.